Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada Mini Market Hikmah Ketegan Tanggulangin - Iin Ilviatul Hikmah; Suci Reza Syafira (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2024)
Hikmah mini market is one of the mini markets located in Sidoarjo, more precisely in Ketegan Tanggulangin. Hikmah mini market provides various kinds of products ranging from food, drinks, kitchen necessities and others. In this thesis research, researchers used quantitative methods which aimed to determine the influence of product quality and service quality on consumer satisfaction at the Hikmah mini market. This research was conducted in Ketegan with consumer respondents who bought or shopped at the Hikmah mini market. In this research, the data collection technique used is non-probability sampling. The sample used was 90 respondents from 900 consumers using the Sovlin calculation formula. This research method uses multiple linear regression with SPSS 25 tools. The results of this research show that product quality and service quality have a significant effect on consumer satisfaction. Simultaneously, product quality and service quality have a significant effect on consumer satisfaction with a coefficient of determination value of 73,4%.